Caracterização por ensaios magnéticos não destrutivos de aços HP provenientes de fornos de reforma - Correa, Mónica Patricia Arenas (2017)
This study aims to characterize, through magnetic tests, the different aging stages to which are submitted HP austenitic steel tubes when operating in oil industry's reformer furnaces. The assumption adopted here is that aging causes microstructural transformations that modify their magnetic properties. The eddy currents technique and a permanent magnetic sensor were used for the HP steel magnetic characterization. The resulting signals, both from eddy currents and sensor were plotted on a contrast map with the purpose of showing a thorough visualization of the different regions, as well as establishing the way that the regions correlate with the material aging state.